HUBUNGAN MODIFIKASI GAYA HIDUP DAN KEPATUHAN KONSUMSI OBAT ANTIDIABETIK DENGAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 DI RS QIM BATANG TAHUN 2013 (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
Diabetes mellitus is a risk factor of cardiovascular diseases. Unhealthy lifestyle have correlation with increased blood glucose of diabetes patients which are less physical exercise, unhealthy diet, tobacco consumption, and alcohol consumption. In addition to lifestyle, the most important factor of blood glucose control is the obedience therapy. This research was to knowed the correlation between lifestyle modification, the obedience of consumption antidiabetic medications and blood glucose of type 2 diabetes mellitus patients. This type of research was explanatory research used a survey method with cross sectional approach, the study sample was patients with diabetes mellitus type 2. Sampling was done by purposive sampling method and obtained sample of 58 sample. The results of the study with the chi-square and fisher test (alpha=0.05) showed that the variables that had a significant correlation with blood glucose levels was the obedience of diet (p=0.019) and obedience antidiabetic medications consumption (p=0.012), variable which not significant correlation was obedience of physical exercise (p=1.000), obedience of smoking cessation (p=0.083). Variable obedience to limit alcohol consumption was not analyzed because the data collected only in one category. Based on the results of these studies suggested the need for guidance and counseling to patients about physical activity, healthy diet, smoking cessation, antidiabetic medications usage and side effects, and the importance of blood glucose control, increase information about diabetes mellitus, complications, and solution.